A beautiful bowl of soup : the best vegetarian recipes / Paulette Mitchell - Mitchell, Paulette
Presents an assortment of vegetarian soup recipes for such dishes as pumpkin soup, onion soup with goat cheese toasts, Mediterranean saffron stew, and Greek spinach and orzo soup.